(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The goal of packet filtering in firewall technology is to sort packets based on packet characteristics. This paper represents the survey on various working models of packet filtering in firewall technology.